Formula and process of environment-friendly brick
By optimizing the raw material system and production process of environmentally friendly bricks, and using shield tunnel mud, river silt, sand washing tailings mud and nano-silicon-based curing agents, we have achieved efficient and stable production of environmentally friendly bricks, solved the problems of low solid waste utilization and large performance fluctuations, improved mechanical properties and dimensional stability, and met green manufacturing standards.
Patent Information
- Application Number
- CN202511364353.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2025-12-16
AI Technical Summary
Existing environmentally friendly bricks suffer from problems such as low solid waste utilization rate, uneven raw material mixing leading to large performance fluctuations, insufficient production process, long curing cycle, and low finished product qualification rate. They are difficult to balance environmental protection and performance stability, and their mechanical properties and dimensional stability are insufficient, failing to meet the needs of high-efficiency production.
Using shield tunnel mud, river silt, and washed sand tailings as the main raw materials, combined with modified stone powder and nano-silicon-based curing agent, a closed-loop manufacturing system is constructed through three-stage drying and screening pretreatment, two-stage roller milling densification, high-pressure rapid molding, and constant temperature and humidity pressure curing, thereby optimizing the homogeneity of raw materials and the production process.
It improves the utilization rate of solid waste and the homogeneity of raw materials, shortens the production cycle, enhances the performance and qualification rate of finished products, reduces resource waste and energy consumption, and meets the requirements of green and low-carbon manufacturing.
Smart Images

Figure BDA0005609953440000131 
Figure BDA0005609953440000141
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of environment-friendly bricks, in particular to a formula and process of environment-friendly bricks. BACKGROUND
[0002] The environment-friendly bricks can meet the basic building functions of walls and floors, reduce energy consumption and carbon emissions in the production process, reduce dependence on natural resources, and have good heat and sound insulation performance, improving the comfort and durability of buildings.
[0003] In the prior art, the utilization rate of solid waste is low, the product performance fluctuates greatly due to uneven mixing of raw materials, the production process has insufficient pretreatment, the curing period is long, and the finished product qualification rate is low, which is difficult to balance environmental protection and performance stability, and the mechanical properties and dimensional stability are insufficient, which cannot meet the efficient production demand. Based on this, the present application provides a formula and process of environment-friendly bricks. SUMMARY
[0004] The purpose of the present application is to provide a formula and process of environment-friendly bricks. The present application optimizes the raw material system, uses the mixture of shield mud, river silt and sand washing tail mud as the main raw material, cooperates with modified stone powder and nano silicon-based curing agent, improves the utilization rate of solid waste and the homogeneity of raw materials, and realizes the refinement of the production process through three-stage drying screening pretreatment, two-stage wheel rolling densification, high-pressure rapid forming and constant temperature and humidity pressure curing, shortens the period and improves the performance of finished products, at the same time, builds a closed-loop system of unqualified product recycling and empty tray board circulation, reduces resource waste and energy consumption, and provides products and processes with environmental protection, high performance and economy.
[0005] To achieve the above purpose, the present application provides the following technical scheme:
[0006] A formula of environment-friendly bricks, calculated by mass fraction, includes: 58-68 parts of a mixture of shield mud, river silt and sand washing tail mud, 22-28 parts of cement, 10-14 parts of modified stone powder, and nano silicon-based curing agent;
[0007] The ratio of the total mass of the nano silicon-based curing agent to the mixture, cement and modified stone powder is 0.0015-0.0025;
[0008] The modified stone powder is treated with 5% silane coupling agent KH-550, the sieve residue amount through a 5mm square hole screen is <10%, and the moisture content is <15%;
[0009] The cement meets the JC / T621-1996 "Cement for Silicate Building Products" standard, the total content of CaO and MgO is ≥75%, the content of MgO is ≤5%, the content of CO2 is ≤5%, and the content of SiO2 is ≤5%, the feed particle size is <15mm, and the fineness is <35% of the sieve residue amount through a 0.049mm square hole screen;
[0010] The residue of the mixture passing through a 0.6mm square-hole sieve is <100%, and the moisture content is <15%.
[0011] Preferably, the process for making environmentally friendly bricks includes the following steps:
[0012] (1) The shield tunnel mud, river silt and washing tailings with a moisture content of 39.86% to 49.88% were poured into the hardened and leveled site. The desiccant was spread manually in three batches and mixed with a loader. The material was piled up and left to dry. The drying environment temperature was 28℃ to 32℃. After drying for 24 hours, the moisture content dropped to 15% to 25%. The drying continued for 48 hours to stabilize the moisture content of the material at 12% to 13%. Impurities were removed by screening with a drum screen to obtain a mixture with uniform particle size.
[0013] (2) The cement is transported to the cement silo for storage;
[0014] (3) The batching machine is used to measure the mixture, cement, modified stone powder and nano-silicon-based curing agent respectively. The nano-silicon-based curing agent is mixed with water at a mass ratio of 1:500 to form a nano-silicon-based curing agent aqueous solution. Then all raw materials and nano-silicon-based curing agent aqueous solution are transported to the roller mill for mixing and stirring.
[0015] (4) The mixed material is transported to the transition bin for storage and then sent to the secondary roller mill for crushing;
[0016] (5) The material after the secondary roller mill is transported to the intermediate chamber in front of the brick press and quantitatively fed into the mold cavity of the press to be pressed into brick blanks;
[0017] (6) The brick blanks are conveyed to the stacker by the belt conveyor, stacked on the pallet, and then transported to the curing area by the mother and child trolleys and the shuttle car;
[0018] (7) Send the trolley containing the brick blanks into the constant temperature and humidity curing room, with a temperature of 80℃, relative humidity of 85% to 90%, and pressure of 0.3MPa to 0.5MPa, and cure for 10 hours.
[0019] (8) After curing, the brick blanks are transported to the finished product storage yard for testing and grading. Unqualified products are broken and reused, and empty pallets are cleaned and returned to the brick press for recycling.
[0020] Preferably, in step (1), the screen size of the drum screen is 0.6 mm, the desiccant is anhydrous calcium chloride with a purity of ≥95%, the first spreading amount is 3% of the total mass of shield mud, river silt and washing tailings, the second is 2%, and the third is 1%.
[0021] Preferably, in step (3), the metering accuracy of the batching machine is ±0.5%, the speed of the roller mill is 20r / min~25r / min, the mixing time is 15min~20min, the material temperature is 25℃~30℃, and the temperature deviation between the aqueous solution of the nano-silicon-based curing agent and the material temperature is ≤±1℃.
[0022] Preferably, in step (4), the rolling pressure of the secondary roller mill is 15MPa to 20MPa, the rolling time is 10min to 15min, and the roller speed is 15r / min to 18r / min.
[0023] Preferably, in step (5), the forming pressure of the brick press is 25MPa to 30MPa, 105 standard bricks are pressed each time, the forming cycle is 20s, and the size of the standard brick is 240mm×115mm×53mm.
[0024] Preferably, in step (6), the conveyor belt speed is 1m / s to 1.5m / s, the conveyor belt width is 800mm, the palletizer stacks 300 to 350 standard bricks per hour, and the pallet size is 1200mm×800mm×20mm.
[0025] Preferably, the constant temperature and humidity curing room in step (7) is equipped with a temperature sensor and a humidity sensor. The temperature detection accuracy is ±0.5℃, and the humidity detection accuracy is ±2%RH. The indoor pressure is regulated by an air compressor with a discharge capacity of 0.8m³. 3 / min.
[0026] Preferably, in step (8), the unqualified products are crushed by a jaw crusher, and the particle size of the crushed material is <5mm. The crusher has a processing capacity of 10t / h.
[0027] Preferably, in step (8), the hollow pallet is returned through the return system. The return system has a conveying speed of 0.8m / s to 1.2m / s and the conveyor belt is made of polyurethane with a thickness of 10mm.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] 1. This invention uses a mixture of shield tunnel mud, river silt, and washed sand tailings as the main raw materials, combined with cement, modified stone powder with controlled particle size and moisture content, and a nano-silicon-based curing agent in a fixed proportion to the total dry material mass. By limiting the particle size distribution and moisture content of the mixture, this invention optimizes the raw material system for environmentally friendly bricks based on solid waste. Compared with existing technologies, this invention can improve the comprehensive utilization rate of solid waste and the homogeneity of raw materials. Therefore, it can solve the problems of low solid waste utilization rate, poor raw material homogeneity, and large performance fluctuations in existing environmentally friendly brick raw material systems.
[0030] 2. This invention employs a pretreatment process combining three-stage desiccant spreading and constant-temperature static drying with drum screening, along with metered addition of a nano-silica-based curing agent aqueous solution, vigorous mixing and densification via two-stage roller milling, high-pressure rapid molding, and accelerated curing under constant temperature and humidity and pressure. Furthermore, it achieves refined and short-cycle stable manufacturing of environmentally friendly bricks by controlling the accuracy of ingredient proportioning, mixing time, roller milling parameters, molding pressure, and curing temperature and humidity throughout the entire process. Compared with existing technologies, this invention can improve product density, mechanical properties, and dimensional stability, while shortening the production cycle and increasing the finished product qualification rate. Therefore, it can solve the problems of long production cycles, low finished product qualification rates, and insufficient mechanical properties and dimensional stability in existing environmentally friendly brick production.
[0031] 3. This invention utilizes a closed-loop manufacturing system that fully recycles defective products after crushing them into raw materials and an automatic empty pallet return system. Combined with precise control and online monitoring of temperature, humidity, and pressure during curing, this system constructs a closed-loop manufacturing system encompassing raw materials, production, finished products, and recycling. Compared with existing technologies, this system can improve raw material utilization and equipment and tooling turnover, while reducing waste emissions and overall energy consumption. Therefore, it can solve the problems of serious resource waste, high energy consumption, and non-compliance with green and low-carbon manufacturing requirements in the current environmentally friendly brick production process. Detailed Implementation
[0032] The technical solutions in the embodiments of the present invention have been clearly and completely described. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] This embodiment provides a formula for an environmentally friendly brick, which, by weight, includes: 58-68 parts of a mixture of shield tunnel mud, river silt and washed sand tailings, 22-28 parts of cement, 10-14 parts of modified stone powder, and nano-silicon-based curing agent.
[0034] The ratio of the nano-silicon-based curing agent to the total mass of the mixture, cement, and modified stone powder is 0.0015 to 0.0025.
[0035] Modified stone powder treated with 5% silane coupling agent KH-550 has a sieve residue of <10% and a moisture content of <15% when passing through a 5mm square hole sieve.
[0036] The cement conforms to the JC / T621-1996 standard "Cement for Silicate Building Products", wherein the total content of CaO and MgO is ≥75%, the content of MgO is ≤5%, the content of CO2 is ≤5%, and the content of SiO2 is ≤5%, the feed particle size is <15mm, and the fineness is that the residue on a 0.049mm square hole sieve is <35%.
[0037] The residue of the mixture passing through a 0.6mm square-hole sieve is <100%, and the moisture content is <15%.
[0038] In some embodiments, the process for making environmentally friendly bricks includes the following steps:
[0039] (1) The shield tunnel mud, river silt and washing tailings with a moisture content of 39.86% to 49.88% were poured into the hardened and leveled site. The desiccant was spread manually in three batches and mixed with a loader. The material was piled up and left to dry. The drying environment temperature was 28℃ to 32℃. After drying for 24 hours, the moisture content dropped to 15% to 25%. The drying continued for 48 hours to stabilize the moisture content of the material at 12% to 13%. Impurities were removed by screening with a drum screen to obtain a mixture with uniform particle size.
[0040] (2) The cement is transported to the cement silo for storage;
[0041] (3) The batching machine is used to measure the mixture, cement, modified stone powder and nano-silicon-based curing agent respectively. The nano-silicon-based curing agent is mixed with water at a mass ratio of 1:500 to form a nano-silicon-based curing agent aqueous solution. Then all raw materials and nano-silicon-based curing agent aqueous solution are transported to the roller mill for mixing and stirring.
[0042] (4) The mixed material is transported to the transition bin for storage and then sent to the secondary roller mill for crushing;
[0043] (5) The material after the secondary roller mill is transported to the intermediate chamber in front of the brick press and quantitatively fed into the mold cavity of the press to be pressed into brick blanks;
[0044] (6) The brick blanks are conveyed to the stacker by the belt conveyor, stacked on the pallet, and then transported to the curing area by the mother and child trolleys and the shuttle car;
[0045] (7) Send the trolley containing the brick blanks into the constant temperature and humidity curing room, with a temperature of 80℃, relative humidity of 85% to 90%, and pressure of 0.3MPa to 0.5MPa, and cure for 10 hours.
[0046] (8) After curing, the brick blanks are transported to the finished product storage yard for testing and grading. Unqualified products are broken and reused, and empty pallets are cleaned and returned to the brick press for recycling.
[0047] In some embodiments, the screen size of the drum screen in step (1) is 0.6 mm, the desiccant is anhydrous calcium chloride with a purity of ≥95%, the first spreading amount is 3% of the total mass of shield mud, river silt and washing tailings, the second is 2%, and the third is 1%.
[0048] In some embodiments, the metering accuracy of the batching machine in step (3) is ±0.5%, the speed of the roller mill is 20r / min to 25r / min, the mixing time is 15min to 20min, the material temperature is 25℃ to 30℃, and the deviation between the temperature of the nano-silicon-based curing agent aqueous solution and the material temperature is ≤±1℃.
[0049] In some embodiments, the rolling pressure of the secondary roller mill in step (4) is 15MPa to 20MPa, the rolling time is 10min to 15min, and the roller speed is 15r / min to 18r / min.
[0050] In some embodiments, the molding pressure of the brick press in step (5) is 25MPa to 30MPa, 105 standard bricks are pressed each time, the molding cycle is 20s, and the size of the standard brick is 240mm×115mm×53mm.
[0051] In some embodiments, the conveying speed of the belt conveyor in step (6) is 1m / s to 1.5m / s, the width of the conveyor belt is 800mm, the palletizer stacks 300 to 350 standard bricks per hour, and the pallet size is 1200mm×800mm×20mm.
[0052] In some embodiments, the constant temperature and humidity curing room in step (7) is equipped with a temperature sensor and a humidity sensor. The temperature detection accuracy is ±0.5℃, and the humidity detection accuracy is ±2%RH. The indoor pressure is regulated by an air compressor with a discharge capacity of 0.8m³. 3 / min.
[0053] In some embodiments, the defective products in step (8) are crushed by a jaw crusher, and the particle size of the crushed material is <5mm. The crusher has a processing capacity of 10t / h.
[0054] In some embodiments, the hollow pallet in step (8) is returned through a return system. The return system has a conveying speed of 0.8m / s to 1.2m / s and the conveyor belt is made of polyurethane with a thickness of 10mm.
[0055] Based on the foregoing embodiments, the following sets of experiments were conducted:
[0056] It should be noted that the raw materials used in the following embodiments are all commercially available.
[0057] Example 1: A formula for an environmentally friendly brick, comprising, by weight, 63 parts of a mixture of shield tunnel mud, river silt and washed sand tailings, 25 parts of cement, 12 parts of modified stone powder, and nano-silicon-based curing agent.
[0058] The ratio of the nano-silicon-based curing agent to the total mass of the mixture, cement, and modified stone powder is 0.002.
[0059] Modified stone powder treated with 5% silane coupling agent KH-550 has a sieve residue of <10% and a moisture content of <15% when passing through a 5mm square hole sieve.
[0060] The cement conforms to the JC / T621-1996 standard "Cement for Silicate Building Products", in which the total content of CaO and MgO is ≥75%, the content of MgO is ≤5%, the content of CO is ≤5% and the content of SiO is ≤5%, the feed particle size is <15mm, and the fineness is that the residue on a 0.049mm square hole sieve is <35%.
[0061] The residue of the mixture passing through a 0.6mm square-hole sieve is <100%, and the moisture content is <15%.
[0062] The manufacturing process of eco-friendly bricks includes the following steps:
[0063] (1) The shield tunnel mud, river silt and washing tailings with a moisture content of 45.0% were poured into the hardened and leveled site. The desiccant was spread manually in three batches and mixed with a loader. The mixture was piled up and left to dry. The drying environment temperature was 30℃. After drying for 24 hours, the moisture content dropped to 20%. The drying continued for 48 hours to stabilize the moisture content of the material at 12.5%. The impurities were removed by screening with a drum screen to obtain a mixture with uniform particle size.
[0064] The screen aperture size of the drum screen is 0.6mm, and the desiccant is anhydrous calcium chloride with a purity of ≥95%. The first spreading amount is 3% of the total mass of shield tunnel mud, river silt and washed sand tailings, the second is 2%, and the third is 1%.
[0065] (2) The cement is transported to the cement silo for storage;
[0066] (3) The batching machine is used to measure the mixture, cement, modified stone powder and nano-silicon-based curing agent respectively. The nano-silicon-based curing agent is mixed with water at a mass ratio of 1:500 to form a nano-silicon-based curing agent aqueous solution. Then all raw materials and nano-silicon-based curing agent aqueous solution are transported to the roller mill for mixing and stirring.
[0067] The metering accuracy of the batching machine is ±0.5%, the speed of the roller mill is 22.5 r / min, the mixing time is 17.5 min, the material temperature is 27.5℃, and the temperature deviation between the aqueous solution of the nano-silicon-based curing agent and the material temperature is ≤±1℃.
[0068] (4) The mixed material is transported to the transition bin for storage and then sent to the secondary roller mill for crushing;
[0069] The rolling pressure of the two-stage roller mill is 17.5 MPa, the rolling time is 12.5 min, and the roller speed is 16.5 r / min.
[0070] (5) The material after the secondary roller mill is transported to the intermediate chamber in front of the brick press and quantitatively fed into the mold cavity of the press to be pressed into brick blanks;
[0071] The brick press has a forming pressure of 27.5MPa, presses 105 standard bricks at a time, has a forming cycle of 20s, and the standard brick size is 240mm×115mm×53mm.
[0072] (6) The brick blanks are conveyed to the stacker by the belt conveyor, stacked on the pallet, and then transported to the curing area by the mother and child trolleys and the shuttle car;
[0073] The conveyor belt has a conveying speed of 1.25m / s and a conveyor belt width of 800mm. The palletizer can stack 325 standard bricks per hour, and the pallet size is 1200mm×800mm×20mm.
[0074] (7) Send the trolley containing the brick blanks into the constant temperature and humidity curing room, with a temperature of 80℃, relative humidity of 87.5%, pressure of 0.4MPa, and curing for 10 hours.
[0075] The constant temperature and humidity curing room is equipped with temperature and humidity sensors. The temperature detection accuracy is ±0.5℃, and the humidity detection accuracy is ±2%RH. The room pressure is regulated by an air compressor with a discharge capacity of 0.8m³. 3 / min.
[0076] (8) After curing, the brick blanks are transported to the finished product storage yard for testing and grading. Unqualified products are broken and reused, and empty pallets are cleaned and returned to the brick press for recycling.
[0077] Non-conforming products are crushed by a jaw crusher. The particle size of the crushed material is <5mm, and the crusher has a processing capacity of 10t / h.
[0078] Empty pallets are returned via a return system with a conveying speed of 1.0 m / s and a conveyor belt made of polyurethane with a thickness of 10 mm.
[0079] Example 2: A formula for an environmentally friendly brick, which, by weight, includes: 58 parts of a mixture of shield tunnel mud, river silt and washed sand tailings, 22 parts of cement, 10 parts of modified stone powder, and nano-silicon-based curing agent.
[0080] The ratio of the nano-silicon-based curing agent to the total mass of the mixture, cement, and modified stone powder is 0.0015;
[0081] Modified stone powder treated with 5% silane coupling agent KH-550 has a sieve residue of <10% and a moisture content of <15% when passing through a 5mm square hole sieve.
[0082] The cement conforms to the JC / T621-1996 standard "Cement for Silicate Building Products", wherein the total content of CaO and MgO is ≥75%, the content of MgO is ≤5%, the content of CO2 is ≤5%, and the content of SiO2 is ≤5%, the feed particle size is <15mm, and the fineness is that the residue on a 0.049mm square hole sieve is <35%.
[0083] The residue of the mixture passing through a 0.6mm square-hole sieve is <100%, and the moisture content is <15%.
[0084] The manufacturing process of eco-friendly bricks includes the following steps:
[0085] (1) The shield tunnel mud, river silt and washing tailings with a moisture content of 39.86% were poured into the hardened and leveled site. The desiccant was spread manually in three batches and mixed with a loader. The material was piled up and left to dry. The drying environment temperature was 28℃. After drying for 24 hours, the moisture content dropped to 15%. The drying continued for 48 hours to stabilize the moisture content of the material at 12%. Impurities were removed by screening with a drum screen to obtain a mixture with uniform particle size.
[0086] The screen aperture size of the drum screen is 0.6mm, and the desiccant is anhydrous calcium chloride with a purity of ≥95%. The first spreading amount is 3% of the total mass of shield tunnel mud, river silt and washed sand tailings, the second is 2%, and the third is 1%.
[0087] (2) The cement is transported to the cement silo for storage;
[0088] (3) The batching machine is used to measure the mixture, cement, modified stone powder and nano-silicon-based curing agent respectively. The nano-silicon-based curing agent is mixed with water at a mass ratio of 1:500 to form a nano-silicon-based curing agent aqueous solution. Then all raw materials and nano-silicon-based curing agent aqueous solution are transported to the roller mill for mixing and stirring.
[0089] The metering accuracy of the batching machine is ±0.5%, the speed of the roller mill is 20 r / min, the mixing time is 15 min, the material temperature is 25℃, and the temperature deviation between the aqueous solution of the nano-silicon-based curing agent and the material temperature is ≤±1℃.
[0090] (4) The mixed material is transported to the transition bin for storage and then sent to the secondary roller mill for crushing;
[0091] The rolling pressure of the two-stage roller mill is 15 MPa, the rolling time is 10 min, and the roller speed is 15 r / min.
[0092] (5) The material after the secondary roller mill is transported to the intermediate chamber in front of the brick press and quantitatively fed into the mold cavity of the press to be pressed into brick blanks;
[0093] The brick press has a forming pressure of 25MPa, presses 105 standard bricks at a time, has a forming cycle of 20s, and the standard brick size is 240mm×115mm×53mm.
[0094] (6) The brick blanks are conveyed to the stacker by the belt conveyor, stacked on the pallet, and then transported to the curing area by the mother and child trolleys and the shuttle car;
[0095] The conveyor belt has a conveying speed of 1m / s and a conveyor belt width of 800mm. The palletizer can stack 300 standard bricks per hour, and the pallet size is 1200mm×800mm×20mm.
[0096] (7) Send the trolley containing the brick blanks into the constant temperature and humidity curing room, with a temperature of 80℃, relative humidity of 85%, pressure of 0.3MPa, and curing for 10 hours.
[0097] The constant temperature and humidity curing room is equipped with temperature and humidity sensors. The temperature detection accuracy is ±0.5℃, and the humidity detection accuracy is ±2%RH. The room pressure is regulated by an air compressor with a discharge capacity of 0.8m³. 3 / min.
[0098] (8) After curing, the brick blanks are transported to the finished product storage yard for testing and grading. Unqualified products are broken and reused, and empty pallets are cleaned and returned to the brick press for recycling.
[0099] Non-conforming products are crushed by a jaw crusher. The particle size of the crushed material is <5mm, and the crusher has a processing capacity of 10t / h.
[0100] Empty pallets are returned via a return system with a conveying speed of 0.8 m / s and a conveyor belt made of polyurethane with a thickness of 10 mm.
[0101] Example 3: A formula for an environmentally friendly brick, calculated by weight, includes: 68 parts of a mixture of shield tunnel mud, river silt and washed sand tailings, 28 parts of cement, 14 parts of modified stone powder, and nano-silicon-based curing agent.
[0102] The ratio of the nano-silicon-based curing agent to the total mass of the mixture, cement, and modified stone powder is 0.0025.
[0103] Modified stone powder treated with 5% silane coupling agent KH-550 has a sieve residue of <10% and a moisture content of <15% when passing through a 5mm square hole sieve.
[0104] The cement conforms to the JC / T621-1996 standard "Cement for Silicate Building Products", wherein the total content of CaO and MgO is ≥75%, the content of MgO is ≤5%, the content of CO2 is ≤5%, and the content of SiO2 is ≤5%, the feed particle size is <15mm, and the fineness is that the residue on a 0.049mm square hole sieve is <35%.
[0105] The residue of the mixture passing through a 0.6mm square-hole sieve is <100%, and the moisture content is <15%.
[0106] The manufacturing process of eco-friendly bricks includes the following steps:
[0107] (1) The shield mud, river silt and washing tailings with a moisture content of 49.88% were poured into the hardened and leveled site. The desiccant was spread manually in three batches and mixed with a loader. The mixture was piled up and left to dry. The drying environment temperature was 32℃. After drying for 24 hours, the moisture content dropped to 25%. The drying continued for 48 hours to stabilize the moisture content of the material at 13%. Impurities were removed by screening with a drum screen to obtain a mixture with uniform particle size.
[0108] The screen aperture size of the drum screen is 0.6mm, and the desiccant is anhydrous calcium chloride with a purity of ≥95%. The first spreading amount is 3% of the total mass of shield tunnel mud, river silt and washed sand tailings, the second is 2%, and the third is 1%.
[0109] (2) The cement is transported to the cement silo for storage;
[0110] (3) The batching machine is used to measure the mixture, cement, modified stone powder and nano-silicon-based curing agent respectively. The nano-silicon-based curing agent is mixed with water at a mass ratio of 1:500 to form a nano-silicon-based curing agent aqueous solution. Then all raw materials and nano-silicon-based curing agent aqueous solution are transported to the roller mill for mixing and stirring.
[0111] The metering accuracy of the batching machine is ±0.5%, the speed of the roller mill is 25 r / min, the mixing time is 20 min, the material temperature is 30℃, and the temperature deviation between the aqueous solution of the nano-silicon-based curing agent and the material temperature is ≤±1℃.
[0112] (4) The mixed material is transported to the transition bin for storage and then sent to the secondary roller mill for crushing;
[0113] The rolling pressure of the two-stage roller mill is 20 MPa, the rolling time is 15 min, and the roller speed is 18 r / min.
[0114] (5) The material after the secondary roller mill is transported to the intermediate chamber in front of the brick press and quantitatively fed into the mold cavity of the press to be pressed into brick blanks;
[0115] The brick press has a forming pressure of 30MPa, presses 105 standard bricks at a time, has a forming cycle of 20s, and the standard brick size is 240mm×115mm×53mm.
[0116] (6) The brick blanks are conveyed to the stacker by the belt conveyor, stacked on the pallet, and then transported to the curing area by the mother and child trolleys and the shuttle car;
[0117] The conveyor belt has a conveying speed of 1.5m / s and a conveyor belt width of 800mm. The palletizer can stack 350 standard bricks per hour, and the pallet size is 1200mm×800mm×20mm.
[0118] (7) Send the trolley containing the brick blanks into the constant temperature and humidity curing room, with a temperature of 80℃, relative humidity of 90%, pressure of 0.5MPa, and curing for 10 hours.
[0119] The constant temperature and humidity curing room is equipped with temperature and humidity sensors. The temperature detection accuracy is ±0.5℃, and the humidity detection accuracy is ±2%RH. The room pressure is regulated by an air compressor with a discharge capacity of 0.8m³. 3 / min.
[0120] (8) After curing, the brick blanks are transported to the finished product storage yard for testing and grading. Unqualified products are broken and reused, and empty pallets are cleaned and returned to the brick press for recycling.
[0121] Non-conforming products are crushed by a jaw crusher. The particle size of the crushed material is <5mm, and the crusher has a processing capacity of 10t / h.
[0122] Empty pallets are returned via a return system with a conveying speed of 1.2 m / s and a conveyor belt made of polyurethane with a thickness of 10 mm.
[0123] Comparative Example 1 differs from Example 1 in that no nano-silicon-based curing agent was added, while the remaining steps are the same as in Example 1.
[0124] Comparative Example 2 differs from Example 1 in that the mixture was not screened by a drum screen, impurities were not removed, and the particle size was uneven. The remaining steps are the same as in Example 1.
[0125] Comparative Example 3 differs from Example 1 in that the curing process is natural curing, with a temperature of around 25°C, a relative humidity of 60% to 70%, no pressure, and a curing time of 7 days. The remaining steps are the same as in Example 1.
[0126] Comparative Example 4 differs from Example 1 in that it does not use a two-stage roller mill for compaction, but only undergoes one roller milling process for mixing, while the remaining steps are the same as in Example 1.
[0127] Performance testing: The environmentally friendly bricks treated in Examples 1, 2, 3, 1, 2, 3 and 4 were subjected to performance tests. The test items included compressive strength, flexural strength, bulk density, water absorption, freeze-thaw cycle performance and thermal conductivity.
[0128] Compressive strength was tested according to GB / T2542-2012 "Test Methods for Masonry Bricks" to assess the compressive strength of environmentally friendly bricks and reflect their load-bearing performance. Flexural strength was also tested according to GB / T2542-2012 "Test Methods for Masonry Bricks" to evaluate the brick's resistance to bending stress and its crack resistance during use. Bulk density was determined according to GB / T2542-2012 "Test Methods for Masonry Bricks" to reflect the density of the brick and affect its thermal conductivity and durability. Water absorption was measured according to GB / T2542-2012 "Test Methods for Masonry Bricks". The test method for environmentally friendly bricks is as follows: The water absorption capacity of the bricks is tested according to GB / T2542-2012 "Test Method for Masonry Bricks". Excessive water absorption can easily lead to freeze-thaw damage and affect service life. Freeze-thaw cycle performance is tested according to GB / T2542-2012 "Test Method for Masonry Bricks". After 25 freeze-thaw cycles, the mass loss rate and strength loss rate of the environmentally friendly bricks are tested to evaluate their durability in cold environments. Thermal conductivity is determined using GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulation Materials - Protective Hot Plate Method", reflecting the thermal insulation performance of the environmentally friendly bricks and relating to building energy-saving effects.
[0129] The obtained test data are recorded in Table 1 below:
[0130]
[0131]
[0132] Performance test results show that Example 1 is in the middle of the range of formulation dosage and process parameters, with balanced and outstanding performance. Examples 2 and 3 are at the two ends of the range of formulation dosage and process parameters, respectively, with no significant fluctuations in performance. The compressive strength and flexural strength are only slightly adjusted within a small range, and the water absorption rate and freeze-thaw cycle loss rate are always kept within a reasonable range. This indicates that the formulation range and process parameter range set by the present invention have good stability and adaptability, and can adapt to the differences in different batches of raw materials and fluctuations in production conditions, providing flexible and reliable technical support for large-scale production.
[0133] Comparative Example 1, lacking the addition of a nano-silica-based curing agent, exhibited a significant decrease in mechanical properties, with compressive and flexural strengths far lower than those of the Example 1. Simultaneously, water absorption increased significantly, and freeze-thaw cycle stability deteriorated. This is because the nano-silica-based curing agent reacts with the active ingredients in the raw materials to form a dense cementitious structure. Its absence increases the internal pores of the brick, reducing structural integrity and directly impacting mechanical properties and impermeability.
[0134] In Comparative Example 2, because the mixture was not screened by a drum screen, the particle size was uneven and impurities were present, resulting in uneven distribution of the internal structure of the brick and the existence of weak areas. This led to a decrease in bulk density and damage to mechanical properties. At the same time, the presence of impurities also increased the water penetration channels, resulting in an increase in water absorption.
[0135] Comparative Example 3 uses natural curing instead of constant temperature and humidity pressure curing, which significantly extends the curing period to 7 days. However, the strength development is insufficient, and the compressive strength and flexural strength are lower than those of the Example. This is because the temperature and humidity are unstable in the natural environment, the cement hydration reaction is slow and insufficient, and the brick cannot form a dense structure. Constant temperature and humidity pressure curing can precisely control the reaction conditions, accelerate the hydration process, and ensure that the brick quickly reaches the design strength.
[0136] Comparative Example 4, due to the omission of the secondary roller mill, resulted in insufficient material mixing and densification, inadequate internal density of the brick, decreased mechanical properties and impermeability, lower compressive strength and flexural strength than the Example, and higher water absorption and freeze-thaw cycle loss rates. This highlights the crucial role of the secondary roller mill in improving material structure and enhancing brick density.
[0137] Comparative analysis of the performance test data from the embodiments and comparative examples reveals that this invention, through optimizing the raw material system, refining the production process, and constructing a closed-loop manufacturing system, not only significantly improves the mechanical properties, durability, and thermal insulation performance of environmentally friendly bricks, but also significantly increases the utilization rate of solid waste, shortens the production cycle, and reduces resource waste and energy consumption, successfully solving the problems in existing environmentally friendly brick production. This demonstrates that the environmentally friendly brick formula and process provided by this invention have significant technical advantages and practical value, can meet the needs of large-scale, green production, have a broader market prospect, and are more suitable for widespread application.
[0138] In the description of this specification, references to terms such as "an experiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that experiment or example is included in at least one experiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same experiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more experiments or examples.
[0139] The preferred experiments disclosed above are merely illustrative of the invention. These preferred experiments do not exhaustively describe all details, nor do they limit the invention to the specific embodiments described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these experiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize it. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A formula for an environmentally friendly brick, characterized in that, The mixture, calculated by weight, includes: 58-68 parts of a mixture of shield tunnel mud, river silt and washed sand tailings, 22-28 parts of cement, 10-14 parts of modified stone powder, and nano-silicon-based curing agent. The ratio of the nano-silicon-based curing agent to the total mass of the mixture, cement, and modified stone powder is 0.0015 to 0.0025. Modified stone powder treated with 5% silane coupling agent KH-550 has a sieve residue of <10% and a moisture content of <15% when passing through a 5mm square hole sieve. The cement conforms to the JC / T621-1996 standard "Cement for Silicate Building Products", wherein the total content of CaO and MgO is ≥75%, the content of MgO is ≤5%, the content of CO2 is ≤5%, and the content of SiO2 is ≤5%, the feed particle size is <15mm, and the fineness is that the residue on a 0.049mm square hole sieve is <35%. The residue of the mixture passing through a 0.6mm square-hole sieve is <100%, and the moisture content is <15%.
2. A process for making environmentally friendly bricks, characterized in that, Using the formula for an environmentally friendly brick as described in claim 1, the process for making the environmentally friendly brick includes the following steps: (1) The shield tunnel mud, river silt and washing tailings with a moisture content of 39.86% to 49.88% were poured into the hardened and leveled site. The desiccant was spread manually in three batches and mixed with a loader. The material was piled up and left to dry. The drying environment temperature was 28℃ to 32℃. After drying for 24 hours, the moisture content dropped to 15% to 25%. The drying continued for 48 hours to stabilize the moisture content of the material at 12% to 13%. Impurities were removed by screening with a drum screen to obtain a mixture with uniform particle size. (2) The cement is transported to the cement silo for storage; (3) The batching machine is used to measure the mixture, cement, modified stone powder and nano-silicon-based curing agent respectively. The nano-silicon-based curing agent is mixed with water at a mass ratio of 1:500 to form a nano-silicon-based curing agent aqueous solution. Then all raw materials and nano-silicon-based curing agent aqueous solution are transported to the roller mill for mixing and stirring. (4) The mixed material is transported to the transition bin for storage and then sent to the secondary roller mill for crushing; (5) The material after the secondary roller mill is transported to the intermediate chamber in front of the brick press and quantitatively fed into the mold cavity of the press to be pressed into brick blanks; (6) The brick blanks are conveyed to the stacker by the belt conveyor, stacked on the pallet, and then transported to the curing area by the mother and child trolleys and the shuttle car; (7) Send the trolley containing the brick blanks into the constant temperature and humidity curing room, with a temperature of 80℃, relative humidity of 85% to 90%, and pressure of 0.3MPa to 0.5MPa, and cure for 10 hours. (8) After curing, the brick blanks are transported to the finished product storage yard for testing and grading. Unqualified products are broken and reused, and empty pallets are cleaned and returned to the brick press for recycling.
3. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (1), the screen size of the drum screen is 0.6 mm, the desiccant is anhydrous calcium chloride with a purity of ≥95%, the first spreading amount is 3% of the total mass of shield mud, river silt and washing tailings, the second is 2%, and the third is 1%.
4. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (3), the metering accuracy of the batching machine is ±0.5%, the speed of the roller mill is 20r / min~25r / min, the mixing time is 15min~20min, the material temperature is 25℃~30℃, and the temperature deviation between the aqueous solution of the nano-silicon-based curing agent and the material temperature is ≤±1℃.
5. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (4), the rolling pressure of the secondary roller mill is 15MPa to 20MPa, the rolling time is 10min to 15min, and the roller speed is 15r / min to 18r / min.
6. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (5), the forming pressure of the brick press is 25MPa~30MPa, 105 standard bricks are pressed each time, the forming cycle is 20s, and the size of the standard brick is 240mm×115mm×53mm.
7. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (6), the conveyor belt speed is 1m / s to 1.5m / s, the conveyor belt width is 800mm, the palletizer stacks 300 to 350 standard bricks per hour, and the pallet size is 1200mm×800mm×20mm.
8. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (7), the constant temperature and humidity curing room is equipped with temperature and humidity sensors. The temperature detection accuracy is ±0.5℃, and the humidity detection accuracy is ±2%RH. The indoor pressure is regulated by an air compressor with a discharge capacity of 0.8m³. 3 / min.
9. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (8), the non-conforming products are crushed by a jaw crusher. The particle size of the crushed material is <5mm, and the crusher has a processing capacity of 10t / h.
10. The process for making an environmentally friendly brick according to claim 2, characterized in that, In step (8), the hollow pallet is returned through the return system. The return system has a conveying speed of 0.8m / s to 1.2m / s and the conveyor belt is made of polyurethane with a thickness of 10mm.